Who has access to urban vegetation? A spatial analysis of distributional green equity in 10 US cities - Nesbitt, Lorien; Meitner, Michael J.; Girling, Cynthia; Sheppard, Stephen R.J.; Lu, Yuhao (Landscape and urban planning, 2019)
[Display omitted] •Access to urban vegetation is most strongly associated with higher education and income.•Racial and ethnic factors show stronger negative associations with urban vegetation in larger cities.•Different types of urban vegetation show different distributional equity patterns.•Parks are more equitably distributed than other vegetation types. This research examines the distributional equity of urban vegetation in 10 US urbanized areas using very high resolution land cover data and census data. Urban vegetation is characterized three ways in the analysis (mixed vegetation, woody vegetation, and public parks), to reflect the variable ecosystem services provided by different types of urban vegetation. Data are analyzed at the block group and census tract levels using Spearman’s correlations and spatial autoregressive models. There is a strong positive correlation between urban vegetation and higher education and income across most cities. Negative correlations between racialized minority status and urban vegetation are observed but are weaker and less common in multivariate analyses that include additional variables such as education, income, and population density. Park area is more equitably distributed than mixed and woody vegetation, although inequities exist across all cities and vegetation types. The study finds that education and income are most strongly associated with urban vegetation distribution but that various other factors contribute to patterns of urban vegetation distribution, with specific patterns of inequity varying by local context. These results highlight the importance of different urban vegetation measures and suggest potential solutions to the problem of urban green inequity. Cities can use our results to inform decision making focused on improving environmental justice in urban settings.